ARUS KAS OPERASI, STRUKTUR MODAL, KINERJA DAN FINANCIAL DISTRESS - Septi Khaenuroh; Muhamad Safiq (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This study was aimed to test whether the effect of Operating Cash Flow, Capital Structure and Corporate Performance in Predicting Financial Distress. This research used a quantitative approach using data from audited financial statements publicly available on the website www.idx.co.id. The population used in this study are a manufacturing base and chemical industry sector, which are 56 companies. The sampling technique used purposive sampling techniques. It acquired sample of 36 companies. The samples in this study were drawn from the period of 2013 and 2014 and obtain 76 data as the unit of analysis (36 x 2 years). The research hypotheses testing using statistical test and logistic regression. The results showed that the variable operating cash flow, capital structure and performance of the company predict financial distress significantly. Operating cash flow and company's performance affect negatively financial distress. Meanwhile, capital structure has positive effect to financial distress.